2017
DOI: 10.3390/ijms19010013
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase Inhibitors from Natural Products and Their Anticancer Potential

Abstract: Telomeres and telomerase are nowadays exploring traits on targets for anticancer therapy. Telomerase is a unique reverse transcriptase enzyme, considered as a primary factor in almost all cancer cells, which is mainly responsible to regulate the telomere length. Hence, telomerase ensures the indefinite cell proliferation during malignancy—a hallmark of cancer—and this distinctive feature has provided telomerase as the preferred target for drug development in cancer therapy. Deactivation of telomerase and telom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 226 publications
(145 reference statements)
0
60
0
Order By: Relevance
“…These metabolites offer clues to manufacture new structural types of antimicrobial and antifungal chemicals that are comparatively safe to humans [62]. The classes of secondary metabolites that have greater antimicrobial properties are flavonoids (flavones, flavonols, flavanols, isoflavones, anthocyanidins), phenolic acids (hydroxybenzoic, hydroxycinnamic acids), stilbenes, lignans, quinones, tannins, coumarins (simple coumarins, furanocoumarins, pyranocoumarins), terpenoids (sesquiterpene lactones, diterpenes, triterpenes, polyterpenes), alkaloids, glycosides, saponins, lectins, steroids, and polypeptides [6,16,56,62,[73][74][75][76][77][78][79][80][81][82][83]. These compounds have copious mechanisms that underlie antimicrobial activity, e.g., disturbing microbial membranes, weakening cellular metabolism, control biofilm formation, inhibiting bacterial capsule production, attenuating bacterial virulence by controlling quorum-sensing, and reducing microbial toxin production [3][4][5][6][73][74][75][76][77][78][79][80][81][82][83][84][85].…”
Section: Bioactive Compounds (Bioactive Phytocomponents)mentioning
confidence: 99%
“…These metabolites offer clues to manufacture new structural types of antimicrobial and antifungal chemicals that are comparatively safe to humans [62]. The classes of secondary metabolites that have greater antimicrobial properties are flavonoids (flavones, flavonols, flavanols, isoflavones, anthocyanidins), phenolic acids (hydroxybenzoic, hydroxycinnamic acids), stilbenes, lignans, quinones, tannins, coumarins (simple coumarins, furanocoumarins, pyranocoumarins), terpenoids (sesquiterpene lactones, diterpenes, triterpenes, polyterpenes), alkaloids, glycosides, saponins, lectins, steroids, and polypeptides [6,16,56,62,[73][74][75][76][77][78][79][80][81][82][83]. These compounds have copious mechanisms that underlie antimicrobial activity, e.g., disturbing microbial membranes, weakening cellular metabolism, control biofilm formation, inhibiting bacterial capsule production, attenuating bacterial virulence by controlling quorum-sensing, and reducing microbial toxin production [3][4][5][6][73][74][75][76][77][78][79][80][81][82][83][84][85].…”
Section: Bioactive Compounds (Bioactive Phytocomponents)mentioning
confidence: 99%
“…However, strong side effects and resistance are commonly reported as responsible for failure of cancer treatment. 4,5 Telomerase is an enzyme composed of two main core subunits-hTR (RNA template subunit) and hTERT (catalytic subunit) responsible for telomere length maintenance by compensating its shortening caused by DNA replication during each cell cycle. 3 Then, telomerase inhibition has become a new potential therapeutic approach.…”
Section: Introductionmentioning
confidence: 99%
“…3 Then, telomerase inhibition has become a new potential therapeutic approach. 4,5 Telomerase is an enzyme composed of two main core subunits-hTR (RNA template subunit) and hTERT (catalytic subunit) responsible for telomere length maintenance by compensating its shortening caused by DNA replication during each cell cycle. 6 Whereas this enzyme is generally absent in normal cells and plays a crucial role in tumour ones, it is a good target for new drugs development.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, we observed an increase in TRF1 and TRF2 protein synthesis in both cell lines tested, which was probably associated with telomere shortening and numerous DNA damage at the chromosome ends. Previous reports found that natural products reduce the telomerase activity suggesting that they can be utilized as a functional food in cancer prevention (Ganesan and Xu 2017). In turn, it was reported that anti-tumor properties are associated with polysaccharides, glucomannans, which ultimately may lead to apoptosis by activation of proapoptotic protein and caspase-dependent pathways (Wasser 2002).…”
Section: Discussionmentioning
confidence: 99%